Cumulative and recent psychiatric symptoms as predictors of substance use onset: does timing matter?. (18th September 2013) - Cerdá, Magdalena; Bordelois, Paula M.; Keyes, Katherine M.; Galea, Sandro; Koenen, Karestan C.; Pardini, Dustin
Abstract Aims We examined two questions about the relationship between conduct disorder (CD), depression and anxiety symptoms and substance use onset: (i) what is the relative influence of recent and more chronic psychiatric symptoms on alcohol and marijuana use initiation and (ii) are there sensitive developmental periods when psychiatric symptoms have a stronger influence on substance use initiation? Design Secondary analysis of longitudinal data from the Pittsburgh Youth Study, a cohort study of boys followed annually from 7 to 19 years of age. Setting Recruitment occurred in public schools in Pittsburgh, Pennsylvania, USA. Participants A total of 503 boys. Measurements The primary outcomes were age of alcohol and marijuana use onset. Discrete‐time hazard models were used to determine whether (i) recent (prior year); and (ii) cumulative (from age 7 until 2 years prior to substance use onset) psychiatric symptoms were associated with substance use onset. Findings Recent anxiety symptoms [hazard ratio (HR) = 1.10, 95% confidence interval (CI) = 1.03–1.17], recent (HR = 1.59, 95% CI = 1.35–1.87), cumulative (HR = 1.45, 95% CI = 1.03–2.03) CD symptoms, and cumulative depression symptoms (HR = 1.04, 95% CI = 1.01–1.08) were associated with earlier alcohol use onset. Recent (HR = 1.39, 95% CI = 1.22–1.58) and cumulative CD symptoms (HR = 1.38, 95% CI = 1.02–1.85) were associated with marijuana use onset. Recent anxiety symptoms were only associated with alcohol use onset among black participants. Conclusions Timing matters in the relationship between psychiatric symptoms and substance use onset in childhood and adolescence, and the psychiatric predictors of onset are substance‐specific. There is no single sensitive developmental period for the influence of psychiatric symptoms on alcohol and marijuana use initiation.